2011
DOI: 10.2753/ijs0020-7659410105
|View full text |Cite
|
Sign up to set email alerts
|

Altar-Bound? The Effect of Disability on the Hazard of Entry into a First Marriage

Abstract: Researchers consistently find that the experience of disability in childhood can influence future life trajectories, particularly with regard to economic and educational outcomes. However, relatively little research has been conducted to explore the effect of disability on other dimensions of the transition to adulthood: namely, its effect on family-formation outcomes. This study uses data from waves I and IV of the National Longitudinal Study of Adolescent Health in order to assess the effect of various types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…23 Prior studies on marriage among people with disabilities have used a variety of definitions of disability, ranging from specific chronic conditions to administrative evidence of workers' compensation claims. [4][5][6][7][8][9]11 The NHIS measure of disability is broad enough to include a variety of conditions limiting adults' activities, and is not explicitly restricted to workrelated limitations, in contrast to data from other large population-based surveys. 23 Nevertheless, future work should consider how marriage outcomes have changed among people with more severe physical impairment than captured by this general measure.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 3 more Smart Citations
“…23 Prior studies on marriage among people with disabilities have used a variety of definitions of disability, ranging from specific chronic conditions to administrative evidence of workers' compensation claims. [4][5][6][7][8][9]11 The NHIS measure of disability is broad enough to include a variety of conditions limiting adults' activities, and is not explicitly restricted to workrelated limitations, in contrast to data from other large population-based surveys. 23 Nevertheless, future work should consider how marriage outcomes have changed among people with more severe physical impairment than captured by this general measure.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…3 Yet, people growing up with disabilities remain less likely than people without disabilities to reach milestones in the transition to adulthood, such as employment, independent living, or marriage. [4][5][6][7][8][9] The present analysis estimated period trends in marriage outcomes of adults with childhood-onset disabilities, hypothesizing that people with disabilities have become better positioned to find and marry a romantic partner, including partners who did not have a disability themselves. Contrary to this hypothesis, data from the last two decades indicated that the retreat from marriage has been especially strong among adults with disabilities, amplifying the disparity in marriage rates by disability status.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations
“…physical, cognitive, social, emotional) and onset of condition. However, women with cognitive impairment may face more barriers than most to meeting a potential mate, forming a lasting cohabiting relationship, and starting a family of their own (Ali et al 2012;Emerson 2007;Hall et al 2005;Kijak 2013;Lesseliers and Van Hove 2002;MacInnes 2011;Young, Gore, and McCarthy 2012). Historically, many women with cognitive impairment were institutionalized and forcibly sterilized to prevent them from forming relationships and having children (Aunos and Feldman 2002).…”
Section: Introductionmentioning
confidence: 99%